Design and testing of iodine cells for metrological laser application - Negriyko, A.M.; Boyko, O.V.; Kachalova, N.M.; Khodakovskiy, V.M.; Klochko, O.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
The design and performance of iodine vapor cells for frequency stabilized laser applications are presented. The traditional design of iodine vapor cell and special development of cell for fluorescence applications are studied. The sets of eight iodine cells developed and filled in Institute of Physics NAS Ukraine were tested in the He-Ne/¹²⁷I₂ frequency stabilized lasers. The nonlinear resonance width and contrasts for different cells were measured. The beat frequency method was used for study of laser output frequency differencies for lasers stabilization using different cells. The results of iodine cells testing shown that for glass cells prepared more than 8 years ago the resonance width is appr. 2.2 MHz and frequency differencies are in the rather narrow area ≤15 kHz. The standard uncertainty of the frequency stabilized He-Ne/¹²⁷I₂ lasers is 11.7 kHz. The tests shown that developed cells meet the demands to applications in metrological lasers.